Enhancing algebraic conceptual knowledge with aid of module using mastery learning approach - Davrajoo, Elenchothy; Ahmad Tarmizi, Rohani; Nawawi, Mokhtar; Hassan, Aminuddin (Elsevier, 2010)
This paper discusses the effect of Algebraic Mastery Learning Module (AMaLM) usage on mathematics achievement of low achievers with high anxiety in mathematics. In this quasi-experimental study, 50 low achievers in Form Four from a secondary school located in a rural area were involved. Target participants were divided into two groups: an experimental group with AMaLM and conventional instruction strategy group. The content of activities for two the groups was the same but differed in its structure of teaching. The activities were carried out for about three weeks of intervention period. The activity papers for conventional instruction (CI) strategy group were solved with the use of only paper-and pencil and compared with the solutions presented by the teachers. The experimental group solved algebra problems also as paper-and pencil activities but utilizing the AMaLM. AMaLM is a self guided book to ease the learning of mathematics for low achievers with mathematics anxiety. It was developed based on constructivist learning theory and mastery learning theory. The material to be learned is subdivided into small units, covering from one lesson to another. The two groups completed Algebraic Comprehension Test (ACT) before and after the intervention period. The mean scores of ACT 1 and ACT II for the AMaLM group and CI group after the intervention were 58.32, 36.88 and 25.8, 22.96 respectively. Results showed that the experimental group improved considerably better than control group. The preliminary findings of this pilot study provided evidence that the construction and mastery of the algebraic concepts assist students towards positive attitude in mathematics learning. AMaLM as self-guided learning tools has favoured the learning process specifically in reinforcing algebraic knowledge for low achiever with anxiety towards mathematics.